Rehabilitation Protocol for Brachial Plexus Injury - Mohd Altaf Mir; Chandrakant Pilania; Taruna Singh; Rahul Kaushik; Devinder Kumar; Labhanshi Aggarwal; Jasanjit Kaur (PT) (Medical Science: Trends and Innovations Vol. 13, 2025)
Brachial plexus injury (BPI) is one of the most serious peripheral nerve injuries, with severe physical disabilities and long-term financial and psychological consequences. Rehabilitation is a cornerstone of BPI management. Rehabilitation is inherently patient-centred and demands consistent adherence. The best outcomes are seen when patients are well-informed, motivated, and actively engaged in their recovery. This chapter discusses a comprehensive Rehabilitation Protocol for Brachial Plexus Injury. Different phases of the Conservative Management Rehabilitation Protocol are discussed in the chapter. Rehabilitation must be individualised and adaptable. To ensure the efficiency of the protocol, therapists must document progress using Medical Research Council (MRC) grading, goniometry for range of movement (ROM), and validated functional outcome scales, e.g Disabilities of Arm, Shoulder and Hand (DASH) score.